BS EN ISO 10893-12 AMD1. Non-destructive testing of steel tubes. Part 12. Automated full peripheral ultrasonic thickness testing of seamless and welded (except submerged arc-welded) steel tubes (2nd September 2019) - British Standards Institution,
No abstract available